THE EFFECT OF AN ESTABLISHED NURSE RESIDENCY PROGRAM ON MEDICATION ERRORS AND FALLS THROUGH TURNOVER - (:unkn) unknown (My University, 2024)
Background: Nurse residency programs (NRPs) have been used by healthcare systems to improve the retention of new graduate RNs for over a decade. With impending nursing shortages and a widening academic-practice gap, The Institute of Medicine (IOM) recommended their implementation in 2011. Along with implementation, the IOM recommended that NRPs be evaluated for their impact on turnover, RN competence, and patient outcomes. NRPs have been shown to positively affect RN turnover and new graduate RN confidence and competence, and studies evaluating the impact on NRPs have focused on these two types of outcomes. There is limited evidence of an NRP’s effect on patient outcomes to date. This study aims to examine the effect of an NRP on two patient outcomes, falls and medication errors, through its effect on turnover. Theory: The Job Demands-Resources Model provides a framework to understand how an organizational resource, such as an NRP, can impact organizational outcomes such as turnover, falls, and medication errors. Methods: A secondary data analysis of a large federally run healthcare system with NRPs in various implementation stages at its medical facilities. Using regression, three models were created to determine the effect of an NRP on turnover, falls, and medication while controlling for hospital complexity, RN hours per patient day, and length of stay. Results: None of the three models were significant (P= 0.93, 0.313, 0.116). ANCOVA did not show a difference in RN turnover, medication errors, or patient falls between established and unestablished NRPs (P= 0.234, 0.114, 0.324). Conclusions: While the results were not significant, continued work and analysis of an NRP’s impact on distal organizational outcomes is needed. Robust studies and methodology must be used to provide a more holistic picture of an NRP’s organizational value.
Keywords: Nursing